You need to find common factors in the equation. First, we factorise the denominator:
![{x}^{2} - x - 2 \: = > (x + 1)(x - 2)](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20-%20x%20-%202%20%5C%3A%20%20%3D%20%20%3E%20%20%28x%20%2B%201%29%28x%20-%202%29)
Which leaves is with the equation:
![y = \frac{(x - 5)(x + 1)(x - 2)}{(x + 1)(x - 2)}](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B%28x%20-%205%29%28x%20%2B%201%29%28x%20-%202%29%7D%7B%28x%20%2B%201%29%28x%20-%202%29%7D%20)
We can see that we have the common factors of (x+1) and (x-2), so these cancel out in the numerator and denominator:
![y = \frac{(x - 5)}{1}](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B%28x%20-%205%29%7D%7B1%7D%20%20)
a.k.a: y = x - 5
So if x+1 and x-2 cancel out, then the x values of the holes are:
x+1=0
x= -1
And
x-2=0
x= 2
Now we plug in each of these numbers into our simplified equation:
y = x - 5
y=(-1)-5
y= -6
This gives us the coordinate (-1,-6)
y = x - 5
y=(2)-5
y= -3
This gives us the coordinate (2,-3)
So the holes are at (-1,-6) and (2,3)